Development and validation of the deep brain stimulation impairment scale (DBS-IS). (March 2017) - Maier, Franziska; Lewis, Catharine J.; Eggers, Carsten; Kühn, Andrea A.; Krug, Henriette; Volkmann, Jens; Kirsch, Anna D.; Wojtecki, Lars; Schnitzler, Alfons; Deuschl, Günther; Krauss, Joachim K.; Woopen, Christiane; et al.
Abstract: Background: Bilateral deep brain stimulation of the subthalamic nucleus (STN-DBS) has considerable influence on motor and non-motor symptoms in Parkinson's disease (PD). While improvements in motor functioning can be easily assessed with general quality of life questionnaires, the measurement of specific STN-DBS-associated impairments often remains insufficient. Hence, we aimed to develop a questionnaire that measures STN-DBS-related impairments. Methods: The development of the (STN-)DBS Impairment Scale (DBS-IS) consisted of four steps. First, 30 semi-structured interviews before, three and twelve months after STN-DBS-surgery were performed to create 76 items that relate to motor and non-motor functioning in STN-DBS PD patients. Second, pilot-testing led to a rewording of the questions for better understanding. Third, a first multicentre survey was performed to reduce items by applying principal component analysis (PCA). Fourth, a second multicentre survey was conducted to examine factor structure, reliability (internal consistency) and validity. Results: After the first survey (N = 215), the PCA lead to a reduction of 54 items. After the second survey (N = 391), exploratory factor analysis determined six factors with 22 items: 1. Postural instability and gait difficulties (5 items), 2. Cognitive impairment (5 items), 3. Speaking problems (3 items), 4. Apathy (3 items), 5. Impulsivity (3 items), and 6. Difficulties related to the DBS device (3 items). High reliability was reported for all subscales (Cronbach's alpha 0.71–0.90). Similarly, construct validity was high (r > 0.50, p < 0.001). Conclusions: With this new questionnaire patients can be followed-up and STN-DBS-specific problems might be adequately measured. Also, comparisons between patients with and without STN-DBS might be possible. Highlights: Development of a new questionnaire for STN-DBS-related impairments. The scale consists of 22 questions and 6 subscales. Subscales: PIGD, cognition, speaking, apathy, impulsivity and DBS-device. Applicable before and after STN-DBS surgery. Comparisons between patients with and without STN-DBS are possible.